Strategy Formulation for Value Added Distributor in Information and Communication Technology Case of PT HDI - Sutanto, Ahmad; Wicaksono, Agung (The Indonesian Journal of Business Administration, 2014)
Abstract - Business role in the ICT industry can be divided into three categories, the manufacturer of the ICT product, distributor who distributed hardware from manufacturer to the reseller or end-user, and the service integrator who deliver ICT product to the end-user. In its development, the distributor is not only distributed the product but also adding value to its product. Some of the value are educated the reseller or end user about the product, doing market research, and providing after sales services to manage user satisfaction. That type of distributor is called Value Added Distributor (VAD). VAD play significant role in the development of ICT Industry. From the manufacturer perspective VAD can boost the product penetration because it is cut the cost of marketing. From the reseller perspective it gives them focus to the existing product to serve and rely to VAD for new product development. From the user perspective it can cut the delivery time because the VAD provide some stock. There are lots of VAD that operate and competing in Indonesia, one of them is PT Helios Distributor Indonesia (HDI). As a new company that established in 2012, HDI facing though condition from the existing VAD. Therefore HDI must formulize the business strategy in order to grow and win the competition. From the research analysis base on PEST writer found that Indonesia still has opportunity for VAD to operate in Indonesia, since the requirement and the regulation of Indonesian government that supporting ICT industry. Focus differentiation for the new product and focus cost differentiation for the mature product is the business level strategy that writer propose for HDI. In term of core competency writer propose 3 core competencies: core competency in term of ability to provide total solution for the customer, ability to build strategic alliance, and ability to analyst market requirement and technology trend forecasting.Â Â Keyword: value added distributor, business level strategy, core competencyÂ